The Hyperlipidemia Caused by Overuse of Glucocorticoid after Liver Transplantation and the Immune Adjustment Strategy - Xueqin Meng; Xinhua Chen; Liming Wu; Shusen Zheng (Journal of Immunology Research)
The overuse of glucocorticoid may cause the metabolic disorders affecting the long term outcome of liver transplantation. This study aims to investigate the immune adjustment strategy by decreasing use of glucocorticoid after liver transplantation. The follow-up study was carried out on liver function and lipid metabolism. This study included adult recipients of liver transplantation. There were 3 groups according to their use of glucocorticoid: long term (>3 months, n=18), short term (<3 months, n=20), and control group (no use of glucocorticoid, radical hepatic resection, n=22). The laboratory results of liver function (AST/ALT ratio) and serum lipid were compared 6 months after liver transplantation. AST/ALT ratio, the marker of liver function, showed no significant difference between long and short term group (P>0.05). The acute rejection had no significant difference between short and long term groups, while TG, HDL, LDL, and glucose showed significant change in the long term group (P<0.05). At 6 months after liver transplantation, the long term group showed higher metabolic disorders (P<0.05). The proper immune adjustment strategy should be made to avoid overuse of glucocorticoid. It can decrease hyperlipidemia and other metabolic disorders after liver transplantation without increasing the acute rejection or liver function damage.